Programmer's ultimate security deskref - Foster, James C. (Syngress Pub., 2004)
The Programmer's Ultimate Security DeskRef is the only complete desk reference covering multiple languages and their inherent security issues. It will serve as the programming encyclopedia for almost every major language in use. While there are many books starting to address the broad subject of security best practices within the software development lifecycle, none has yet to address the overarching technical problems of incorrect function usage. Most books fail to draw the line from covering best practices security principles to actual code implementation. This book bridges that gap and covers the most popular programming languages such as Java, Perl, C++, C, and Visual Basic. * Defines the programming flaws within the top 15 programming languages. * Comprehensive approach means you only need this book to ensure an application's overall security. * One book geared toward many languages.